Method for controlling impurity elements in smelting process of niobium-hafnium alloy

Through the composite control strategy of dynamic frequency modulation and variable current and the use of intermediate frequency electromagnetic field, a spiral electromagnetic force field is formed, which solves the problems of impurity elements reaction and component segregation in niobium hafnium alloy smelting, realizes the uniformity and stability of alloy components, and reduces production costs.

CN119876678AInactive Publication Date: 2025-04-25SHAANXI ZHONGHENG WEICHUANG METAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510285285.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There are problems in the existing niobium hafnium alloy smelting process, impurity element reaction, component segregation, high raw material purity requirements, high production costs and evaporation losses, resulting in uneven product performance and unstable quality.

Method used

The composite control strategy of dynamic frequency regulation and variable current is adopted, and the electromagnetic field parameters are adjusted in real time through the calculation formula of frequency and temperature coupling to form a spiral electromagnetic force field with specific orientations. Combined with the use of medium frequency electromagnetic field and refining agent, melt purification and temperature regulation are carried out, and finally cast and fast solidification are carried out through the preheated flow guide.

Benefits of technology

It significantly improves the impurity separation efficiency, improves the uniformity and stability of alloy components, reduces production costs, and improves the economic and efficiency of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876678A_ABST
    Figure CN119876678A_ABST
Patent Text Reader

Abstract

The invention discloses a method for controlling impurity elements in the smelting process of niobium-hafnium alloy, and belongs to the technical field of alloy materials. The method comprises the steps that niobium-hafnium raw materials are dried in an inert atmosphere and then mechanically ground, and vacuum induction heating is adopted for smelting; a refining agent is added, and a medium-frequency electromagnetic field is applied for melt purification; after the slagging-off operation is completed, target elements are added, and temperature regulation and control are conducted; and pouring and quickly solidifying through a preheated flow guide pipe. According to the scheme, the impurity separation efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of alloy materials, and in particular to a method for controlling impurity elements in a niobium-hafnium alloy smelting process. Background Art

[0002] With the rapid development of high-tech fields such as aerospace and nuclear industry, the demand for high-temperature load-bearing materials is becoming increasingly urgent. Niobium and hafnium alloys have become the preferred materials for key components such as aerospace engine nozzles and reactor components due to their excellent high-temperature strength, good oxidation resistance and unique physical and chemical properties. In the preparation process of niobium and hafnium alloys, the quality control of the smelting process directly affects the performance of the final product. In the existing technology, the smelting of niobium and hafnium alloys mainly adopts vacuum consumable arc melting, electron beam melting and plasma arc melting. However, these traditional smelting methods have many technical difficulties in practical application: first, due to the high melting point characteristics and active chemical properties of niobium and hafnium, they are very easy to react with impurity elements such as oxygen, nitrogen, and carbon during the smelting process to form various difficult-to-remove oxides, nitrides, and carbides. These inclusions seriously affect the comprehensive performance of the alloy; second, the uneven temperature field during the smelting process leads to serious segregation of alloy components, affecting the uniformity and stability of the product; third, in the traditional smelting process, the purity of the raw materials is extremely high, which not only greatly increases the production cost, but also is limited by the supply of high-purity raw materials, restricting industrial development; in addition, the evaporation loss problem in the smelting process is also a technical problem that needs to be solved urgently. Especially under high temperature conditions, the selective evaporation of active elements such as hafnium will make it difficult to control the composition and affect the consistency of product quality.

[0003] In response to the above technical problems, the researchers have made a lot of process improvements and technological innovations. For example, by optimizing the vacuum control strategy and adopting a multi-stage vacuum pumping-inert gas circulation process, the gas impurity content in the smelting process is effectively reduced; by developing a new composite slag-making agent system, the purification efficiency of the melt is improved, and the content of impurity elements such as oxygen and nitrogen is significantly reduced; by adopting electromagnetic stirring technology, the temperature field distribution of the molten pool is improved, and the occurrence of segregation is reduced. However, these improvement measures still have some technical limitations: first, although the use of composite slag-making agents can effectively absorb impurity elements, it will also introduce new inclusions, and the selection of slag system needs to comprehensively consider multiple factors such as melting point, viscosity, chemical activity, etc., and the optimization of process parameters is difficult; second, although electromagnetic stirring can improve the temperature field distribution, the equipment structure is complex, the energy consumption is high, and the reliability of the electromagnetic coil faces severe challenges under high temperature conditions; third, although the multi-stage vacuum-inflation cycle process can reduce the gas impurity content, it prolongs the production cycle, reduces production efficiency, and increases energy consumption; in addition, solving a technical problem may cause new problems. For example, the high vacuum process used to reduce the oxygen content aggravates the evaporation loss of active elements. Therefore, how to find the optimal balance between various process parameters, achieve precise control of impurity elements, and ensure production efficiency and economy at the same time, is still the focus and difficulty of current research.

[0004] Therefore, a technical solution is urgently needed to improve the impurity separation efficiency. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the embodiment of the present application provides a method for controlling impurity elements in the smelting process of niobium-hafnium alloy. The present application solves the technical problems of the prior art such as unreasonable field intensity distribution and insufficient impurity separation.

[0006] The embodiment of the present application provides a method for controlling impurity elements in the smelting process of niobium and hafnium alloy, comprising: drying the niobium and hafnium raw materials under an inert atmosphere, mechanically grinding them, and smelting them by vacuum induction heating; adding a refining agent and applying a medium-frequency electromagnetic field to purify the melt; after completing the slag removal operation, adding target elements and controlling the temperature; pouring through a preheated guide tube and rapidly solidifying.

[0007] In a possible implementation, the niobium and hafnium raw materials are dried in an inert atmosphere and then mechanically ground, and then smelted using vacuum induction heating, including: selecting high-grade industrial niobium and pure hafnium, transferring the raw materials into a ball mill for mechanical grinding under argon protection; smelting in a medium-frequency vacuum induction furnace according to a prescribed melting control program, and coating the inner wall of the smelting crucible with an yttrium oxide protective layer.

[0008] In a possible implementation, a refining agent is added and a medium-frequency electromagnetic field is applied to purify the melt, including: adding a refining agent consisting of calcium fluoride, yttrium oxide and magnesium fluoride to a molten niobium-hafnium alloy; refining under the condition of applying a medium-frequency electromagnetic field, so as to utilize electromagnetic force to generate directional flow to promote the aggregation and floating of inclusions; and completing the slag removal operation under the protection of argon gas.

[0009] In a possible implementation, refining is performed under the condition of applying a medium-frequency electromagnetic field, including: using a water-cooled copper tube to make an induction coil, and winding the induction coil evenly along the axial direction of the crucible; arranging a high-purity quartz glass insulating sleeve between the coil and the crucible, and controlling the electromagnetic field by adjusting the frequency and current intensity.

[0010] In a possible implementation, in which refining is performed under the condition of applying a medium frequency electromagnetic field, it also includes: controlling the electromagnetic force distribution by adjusting the phase difference of the three-phase power supply, setting the phase difference of the three-phase power supply to a reference phase, an advanced reference phase and a lagging reference phase, respectively, to form a spirally ascending electromagnetic force field.

[0011] In a possible implementation, refining is carried out under the condition of applying a medium frequency electromagnetic field, and also includes: maintaining a high electromagnetic field intensity for strong stirring in the early stage of the refining process, then gradually reducing the electromagnetic field intensity, stabilizing the electromagnetic field intensity within a specific range at the end of refining, and controlling the melt flow rate.

[0012] In one possible implementation, after the slag removal operation is completed, the target elements are added and the temperature is controlled, including: adding alloy elements containing tantalum and tungsten with target purity to the melt, and using a feeding device to control the feeding rate; stirring through a medium frequency electromagnetic field to ensure that the alloy elements are evenly distributed, and performing heating, insulation and cooling treatments in turn.

[0013] In a possible implementation, casting and rapid solidification are performed through a preheated flow guide tube, including: selecting flow guide tubes of different lengths and preheating temperatures according to the hafnium content, the flow guide tube is made of high-purity zirconium oxide material and preheated by electromagnetic induction heating, and is coated with a thermal insulation protective layer on the outside, and a bottom pouring system is used for casting under argon protection.

[0014] In a possible implementation, wherein guide tubes of different lengths and preheating temperatures are selected according to the hafnium content, comprising: the preheating temperature of the guide tube is determined according to the hafnium content, a low preheating temperature is configured when the hafnium content is lower than a preset value, and a high preheating temperature is configured when the hafnium content is higher than the preset value, preheating is performed by medium frequency induction heating, and the outside of the guide tube is coated with a protective layer made of a composite material of zirconium oxide and yttrium oxide.

[0015] In a possible implementation, a bottom pouring system is used for pouring under argon protection, comprising:

[0016] The bottom pouring system uses a water-cooled copper mold to rapidly solidify during the pouring process, and the pouring chamber is filled with high-purity argon gas and maintained at a constant pressure. The pouring process is completed by controlling the pouring rate and the temperature and flow rate of cooling water.

[0017] In a method for controlling impurity elements in the smelting process of a niobium-hafnium alloy as provided above, the embodiment of the present application adopts a composite control strategy of dynamic frequency modulation and variable current, and adjusts the electromagnetic field parameters in real time through a calculation formula of frequency and temperature coupling to ensure that the intensity of the electromagnetic force always matches the physical properties of the melt. By setting a three-phase power supply with an asymmetric phase difference, a spiral electromagnetic force field with a specific orientation is formed in the melt. This force field distribution can provide a stable motion trajectory for the migration of impurities. At the same time, the axial gradient electromagnetic force field intensity distribution is adopted to avoid the eddy current dead zone under the traditional uniform field strength. In the process, the precise control of the electromagnetic field is achieved through reasonable coil structure design and the arrangement of the flux compensation device. Especially at the end of refining, the exponential law is used to reduce the field strength to avoid violent fluctuations in the melt. Through the technical solution of multi-parameter coordinated control, the problem of unsatisfactory electromagnetic field effect in the prior art is solved, and the impurity separation efficiency is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 A schematic flow chart of a method for controlling impurity elements in a niobium-hafnium alloy smelting process provided in an embodiment of the present application;

[0020] Figure 2 A SEM morphology image of a conventional arc melting method provided in an embodiment of the present application;

[0021] Figure 3 A TEM image of a niobium-hafnium alloy provided in an embodiment of the present application;

[0022] Figure 4 An EDS analysis diagram of impurity element distribution provided in an embodiment of the present application;

[0023] Figure 5 An EBSD analysis diagram of grain boundary orientation distribution provided in an embodiment of the present application;

[0024] Figure 6 An energy spectrum analysis diagram of an impurity phase component provided in an embodiment of the present application. DETAILED DESCRIPTION

[0025] Various exemplary embodiments of the present disclosure will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present disclosure unless otherwise specifically stated.

[0026] Those skilled in the art can understand that the terms "first", "second" and the like in the embodiments of the present disclosure are only used to distinguish different steps, devices or modules, etc., and neither represent any specific technical meaning nor represent the necessary logical order between them. It should also be understood that in the embodiments of the present disclosure, "multiple" can refer to two or more, and "at least one" can refer to one, two or more. It should also be understood that for any component, data or structure mentioned in the embodiments of the present disclosure, in the absence of explicit limitation or contrary revelation given in the context, it can generally be understood as one or more. In addition, the term "and / or" in the present disclosure is only a description of the association relationship of the associated objects, indicating that there can be three relationships, for example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present disclosure generally indicates that the associated objects before and after are an "or" relationship. It should also be understood that the description of each embodiment in the present disclosure emphasizes the differences between the embodiments, and the same or similar parts can refer to each other. For the sake of brevity, they will not be repeated one by one.

[0027] At the same time, it should be understood that, for ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present disclosure and its application or use. The techniques, methods and devices known to ordinary technicians in the relevant fields may not be discussed in detail, but where appropriate, the techniques, methods and devices should be considered part of the specification. It should be noted that similar numbers and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in subsequent drawings.

[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0029] Figure 1A schematic flow chart of a method for controlling impurity elements in a niobium-hafnium alloy smelting process provided in an embodiment of the present application.

[0030] It should be understood that in the conventional technical solutions such as the smelting and purification methods of niobium and hafnium elements in high-temperature alloys currently used in the mainstream, the melt purification treatment mainly relies on fixed-frequency electromagnetic stirring. For example, medium-frequency induction heating with a constant frequency of 10kHz is used, and the current intensity is maintained at 550A; or a single frequency in the range of 8-15kHz is used with a fixed current of 450-650A for treatment. These solutions have obvious technical bottlenecks in practical applications: when the melt temperature rises to above 2480℃, the conductivity of the melt will change nonlinearly with temperature, but the electromagnetic field of fixed frequency and current cannot adjust its action intensity in a targeted manner, resulting in an imbalance in the distribution of electromagnetic forces in high-temperature areas. At the same time, the conventional three-phase 120° uniform phase difference configuration used in these solutions forms symmetrical annular vortices in the melt. Although basic stirring effects can be achieved, the annular vortices will form a stable stagnation zone near the crucible wall, inhibiting the effective separation of impurities. Especially when processing alloys with high hafnium content (hafnium mass fraction greater than 70%), due to the high density of hafnium, the traditional uniform electromagnetic field is difficult to provide sufficient upward thrust to overcome the effect of gravity, resulting in a significant reduction in the floating speed of impurities.

[0031] Another key issue is the insufficient compensation for magnetic field inhomogeneity. For example, only one compensation coil is set at the top and bottom of the crucible, and the compensation current phase adopts a fixed value of 180°. This simple compensation method is difficult to cope with the complex distribution of the electromagnetic field in the melt. In actual production, it is found that this compensation method will cause obvious field intensity fluctuations in the middle area of ​​the crucible, and the compensation effect will deteriorate rapidly with the increase of melt temperature. In addition, the existing technical solutions generally adopt the method of directly cutting off the power or linearly reducing the field strength at the end of refining. This simple ending method will cause violent surface fluctuations of the melt, and the separated impurities are easily drawn into the deep part of the melt. For example, the method of linearly reducing the field strength within 30 seconds is adopted. In actual applications, it is found that this field reduction method will produce a lateral velocity component on the surface of the melt, which interferes with the normal floating path of impurities.

[0032] In contrast, the dynamic frequency modulation and variable current coupling control technology adopted in the embodiment of the present application realizes the real-time matching of electromagnetic field parameters and melt temperature through the dynamic frequency adjustment formula. In particular, by setting an asymmetric three-phase power supply configuration with an advanced phase of 119.5-120.8° and a lagging phase of 119.2-120.5°, a directional spiral rising electromagnetic force field is generated in the melt. This special force field distribution can effectively break the limitations of traditional symmetrical eddy currents. At the same time, through the field intensity distribution function, a gradient-changing electromagnetic force field is formed in the axial direction, providing a continuous and stable driving force for the directional migration of impurities. In terms of magnetic field compensation, a 10-12 turn distributed compensation coil is used, with a compensation current ratio of 0.42-0.48 times and a phase lag angle of 132-135°, to achieve a full range of dynamic field intensity balance. This multi-parameter coordinated precise control scheme overcomes the technical defects of unreasonable field intensity distribution and insufficient impurity separation in the prior art.

[0033] like Figure 1 As shown, in step S101, the niobium and hafnium raw materials are dried in an inert atmosphere, then mechanically ground, and melted by vacuum induction heating.

[0034] In one embodiment, high-grade pure industrial niobium and pure hafnium are selected, and the raw materials are transferred into a ball mill for mechanical grinding under argon protection; a medium-frequency vacuum induction furnace is used for smelting according to a prescribed melting control program, and an yttrium oxide protective layer is coated on the inner wall of the smelting crucible.

[0035] Specifically, the raw materials of niobium and hafnium alloy are prepared according to the composition requirements, and high-grade industrial niobium and pure hafnium are selected as raw materials. The raw materials need to be screened. The raw materials are placed in a vacuum drying oven and dried at a temperature of 85-95°C for 4.5-5 hours to remove surface moisture. The dried raw materials are temporarily stored in a sealed container protected by argon. Under an argon atmosphere, the raw materials are transferred to a ball mill for mechanical grinding, and the grinding time is controlled to be about 2.5 hours. High-purity argon is used for protection during the grinding process, the purity of argon is ≥99.99%, and the gas pressure is maintained in the range of 0.08-0.12MPa. The ground powder is melted in a medium-frequency vacuum induction furnace according to the prescribed melting control program, and the melting temperature is controlled between 2450-2520°C. During the smelting process, vacuum induction heating is used to reduce impurities, and the vacuum degree is maintained in the range of 8.5×10-2-9.2×10-2Pa. During smelting, a zirconium oxide crucible is used, and the inner wall of the crucible is coated with a layer of yttrium oxide protective layer, and the coating thickness is controlled between 0.15-0.22mm.

[0036] In step S102, a refining agent is added and a medium frequency electromagnetic field is applied to purify the melt.

[0037] Specifically, a refining agent consisting of calcium fluoride, yttrium oxide and magnesium fluoride is added to the molten niobium-hafnium alloy; refining is carried out under the condition of applying a medium-frequency electromagnetic field to utilize electromagnetic force to generate directional flow to promote inclusion aggregation and floating; and slag removal is completed under argon protection.

[0038] In one embodiment, refining is performed under the condition of applying a medium-frequency electromagnetic field, including: using a water-cooled copper tube to make an induction coil, and winding the induction coil evenly along the axial direction of the crucible; arranging a high-purity quartz glass insulating sleeve between the coil and the crucible, and controlling the electromagnetic field by adjusting the frequency and current intensity.

[0039] In another embodiment, refining is performed under the condition of applying a medium frequency electromagnetic field, and also includes: controlling the electromagnetic force distribution by adjusting the phase difference of the three-phase power supply, setting the phase difference of the three-phase power supply to a reference phase, an advanced reference phase and a lagging reference phase, respectively, to form a spirally ascending electromagnetic force field.

[0040] In another embodiment, refining is performed under the condition of applying a medium frequency electromagnetic field, and also includes: maintaining a high electromagnetic field intensity for strong stirring in the early stage of the refining process, then gradually reducing the electromagnetic field intensity, stabilizing the electromagnetic field intensity within a specific range at the end of refining, and controlling the melt flow rate.

[0041] Preferably, for melt purification treatment, a refining agent can be added to the molten niobium-hafnium alloy for purification, and the melt can be moved in a directional manner by magnetization. The refining agent is composed of calcium fluoride, yttrium oxide and magnesium fluoride, with a mass ratio of 3.5:1.5:1. The amount of refining agent added is 0.35-0.42% of the mass of the melt. During the refining process, the melt temperature is controlled within the range of 2480-2510°C, and a medium-frequency electromagnetic field of 8-12kHz is applied. Refining agent is added to remove slag inclusions, and magnetization is used to directional move the melt, which is conducive to precipitation and slag removal. The refining time is controlled within 25-32 minutes. During the refining process, the melt is directional flowed by the action of electromagnetic force, which promotes the aggregation and floating of inclusions. After the refining is completed, the temperature and vacuum degree are kept unchanged, and the mixture is left to stand for 15-18 minutes to allow the inclusions to fully float. Then the slag discharge port is opened, and the slag removal operation is completed under the protection of argon. During the slagging process, the argon pressure was maintained in the range of 0.08-0.12MPa and the gas flow rate was controlled at 2.5-3.2L / min.

[0042] Further, in one embodiment, during the melt purification process, the control of the medium frequency electromagnetic field needs to be implemented in sequence according to the following steps: First, the induction coil is evenly wound along the axial direction of the crucible, the number of coil turns is 16-18 turns, and the distance between adjacent coils is maintained at 12.5-13.8 mm. The induction coil is made of a water-cooled copper tube, the outer diameter of the copper tube is 12.5-13.2 mm, the inner diameter is 8.8-9.2 mm, and the cooling water flow rate is maintained at 8.5-9.2 L / min. A high-purity quartz glass insulating sleeve is set between the coil and the crucible, and the sleeve wall thickness is 3.8-4.2 mm.

[0043] The application of the medium frequency electromagnetic field starts with the addition of the refining agent, with the initial frequency set to 9.5kHz and the current intensity to 580-620A. As the refining process proceeds, the frequency and current intensity are dynamically adjusted according to the change in melt temperature. The frequency adjustment uses the following calculation formula:

[0044] Where f(t) is the frequency at time t (Hz), T(t) is the melt temperature at time t (℃), and t is the refining time (min). Adjustment is performed, where I(t) is the current intensity (A) at time t.

[0045] The electromagnetic force distribution generated by the medium frequency electromagnetic field is controlled by adjusting the phase difference of the three-phase power supply. The phase difference of the three-phase power supply is set in sequence: the first phase is the reference phase 0°, the second phase is 119.5-120.8° ahead of the reference phase, and the third phase is 119.2-120.5° behind the reference phase. Through this asymmetric phase difference setting, a spiral rising electromagnetic force field is formed in the melt. The distribution of the electromagnetic force field intensity E with the axial height z satisfies:

[0046] Where E0 is the bottom electromagnetic force field strength, ranging from 1.15-1.28T, and h is the melt height.

[0047] In the first 15 minutes of the refining process, the electromagnetic field intensity is maintained at a high level to produce a strong electromagnetic stirring effect on the melt. After that, the electromagnetic field intensity is gradually reduced at a rate of 0.028-0.032T per minute. When the refining time reaches 25 minutes, the electromagnetic field intensity is stabilized at 0.62-0.68T and maintained until the end of refining. At this stage, the flow rate of the melt is controlled at 385-425mm / s, and the Reynolds number is maintained at 3.8×10 4 -4.2×10 4 within the range.

[0048] To ensure the uniformity of the electromagnetic field, a magnetic flux compensation device is arranged around the crucible. The compensation coil is wound with flat copper wire with a cross-sectional area of ​​6.5×2.8mm 2The number of turns is 10-12 turns. The axial position of the compensation coil is symmetrically arranged up and down relative to the main induction coil, and the axial spacing is 32-36mm. The compensation current intensity is 0.42-0.48 times that of the main induction current, and the phase lags the main induction current by 132-135°. Through flux compensation, the radial unevenness of the electromagnetic field in the melt is controlled within 5.8%. In the static stage after the refining is completed, the electromagnetic field intensity is gradually reduced to zero according to the exponential law. The reduction process lasts for 5-6 minutes to avoid violent fluctuations in the melt.

[0049] In step S103, after the slagging operation is completed, the target element is added and the temperature is controlled.

[0050] In one embodiment, alloy elements including tantalum and tungsten with target purity are added to the melt, and a feeding device is used to control the feeding rate; stirring is performed by a medium-frequency electromagnetic field to uniformly distribute the alloy elements, and heating, insulation and cooling treatments are performed in sequence.

[0051] Specifically, after the slag removal operation is completed, alloying elements can be added to change the thermodynamic state of the melt. Alloying elements with a purity of ≥99.95% are added to the melt, including tantalum, tungsten, etc. The amount of tantalum added is 0.38-0.45% of the mass of the melt, and the amount of tungsten added is 0.18-0.25% of the mass of the melt. The alloying process is carried out at a temperature of 2485-2515℃, and the vacuum degree is maintained in the range of 9.2×10-2-9.8×10-2Pa. When adding alloying elements, a special feeding device is used, and the feeding rate is controlled at 38-45g / min. During the alloying process, stirring is carried out by a medium-frequency electromagnetic field to ensure uniform distribution of the alloying elements. The stirring power is controlled at 18-22kW, and the stirring time is 15-20 minutes. After alloying, the melt temperature was raised to 2520-2540°C, kept at this temperature for 10-12 minutes, and then cooled to 2465-2485°C at a rate of 4.5-5.2°C / min.

[0052] Table 1 Main parameters of alloying endpoint

[0053] Tantalum content / % Tungsten content / % Temperature / ℃ Vacuum degree / Pa Inclusions / % Alloying rate / % 0.382 0.182 2475 9.22E-2 0.32 97.8 0.395 0.195 2472 9.35E-2 0.30 98.2 0.408 0.208 2470 9.42E-2 0.28 98.5 0.422 0.218 2468 9.52E-2 0.25 98.8 0.435 0.228 2467 9.62E-2 0.22 99.1 0.442 0.235 2466 9.72E-2 0.20 99.3 0.448 0.242 2465 9.78E-2 0.18 99.5 0.450 0.248 2465 9.82E-2 0.15 99.6

[0054] As shown in Table 1, when the tantalum content gradually increases from 0.382% to 0.450%, and the tungsten content increases from 0.182% to 0.248% accordingly, the thermodynamic state of the melt shows a regular change. The melt temperature shows a nonlinear decreasing trend with the increase of the alloy element content. Specifically, in the range of tantalum content of 0.382-0.422%, the temperature drops from 2475℃ to 2468℃, and the cooling rate is relatively fast; while in the range of tantalum content of 0.422-0.450%, the temperature decrease trend tends to be gentle, and finally stabilizes at 2465℃. This temperature change characteristic is closely related to the thermodynamic equilibrium state of the melt.

[0055] In terms of vacuum control, as the content of alloy elements increases, the vacuum shows a steady upward trend. When the tantalum content is 0.382%, the vacuum is maintained at 9.22×10-2Pa; when the tantalum content increases to 0.450%, the vacuum is increased to 9.82×10-2Pa. The increase in vacuum helps to reduce the gas impurity content in the melt.

[0056] The inclusion content shows a characteristic of continuously decreasing with the increase of alloying element addition. When the tantalum and tungsten contents are at a low level (tantalum 0.382%, tungsten 0.182%), the inclusion content is 0.32%; as the alloying element content increases, the inclusion content gradually decreases, and when the final tantalum content reaches 0.450% and the tungsten content reaches 0.248%, the inclusion content drops to 0.15%. This trend of decreasing inclusion content forms a good synergistic effect with the increase in vacuum and the change in temperature.

[0057] As an important indicator to measure the process effect, the alloying rate shows the characteristic of increasing with the increase of alloying element content. In the initial stage (0.382% tantalum and 0.182% tungsten), the alloying rate is 97.8%; as the content of alloying elements increases, the alloying rate gradually increases, and finally reaches 99.6% when the tantalum content is 0.450% and the tungsten content is 0.248%.

[0058] In step S104, pouring is performed through the preheated flow guide tube and rapidly solidifies.

[0059] In one embodiment, flow guide tubes of different lengths and preheating temperatures are selected according to the hafnium content. The flow guide tubes are made of high-purity zirconium oxide material and preheated by electromagnetic induction heating. The outside is covered with a thermal insulation protective layer and cast using a bottom pouring system under argon protection.

[0060] Furthermore, in another embodiment, flow guide tubes of different lengths and preheating temperatures are selected according to the hafnium content, including: the preheating temperature of the flow guide tube is determined according to the hafnium content, a low preheating temperature is configured when the hafnium content is lower than a preset value, and a high preheating temperature is configured when the hafnium content is higher than the preset value, preheating adopts medium frequency induction heating, and the outside of the flow guide tube is coated with a protective layer made of a composite material of zirconium oxide and yttrium oxide.

[0061] In another embodiment, a bottom pouring system is used for pouring under argon protection, including: the bottom pouring system performs rapid solidification through a water-cooled copper mold during the pouring process, the pouring chamber is filled with high-purity argon and maintains a constant pressure, and the pouring process is completed by controlling the pouring rate and the cooling water temperature and flow rate.

[0062] For pouring the regulated melt with a guide tube with reasonable diameter, length, roughness and other requirements, preferably, the guide tube can be made of high-purity zirconium oxide material with an internal roughness better than Ra0.2. The geometric dimensions of the guide tube are: when the hafnium content is ≤70wt%, the guide tube length is 48-65mm; when the hafnium content is greater than 70wt%, the guide tube length is 32-45mm. The guide tube is preheated by electromagnetic induction heating, and the preheating temperature range is: when the hafnium content is ≤70wt%, the preheating temperature is 1200-1350℃; when the hafnium content is greater than 70wt%, the preheating temperature is 1450-1580℃. The guide tube is preheated by medium-frequency induction heating with a power of 4.2-5.5kW. The outside of the guide tube is coated with a thermal insulation protective layer, which is made of a composite material of zirconium oxide and yttrium oxide with a thickness of 0.8-1.2mm. During the pouring process, the melt temperature is controlled at 2445-2475℃, and the pouring rate is 2.2-2.8kg / min. A bottom pouring system is used for pouring, and the pouring chamber is filled with high-purity argon gas, and the pressure is maintained at 0.08-0.12MPa. During the pouring process, rapid solidification is carried out through a water-cooled copper mold, and the cooling water temperature is controlled at 18-22℃, and the flow rate is 42-58L / min. The entire pouring process lasts 28-35 minutes.

[0063] Figure 2 This is a SEM morphology image of a conventional arc melting method provided in the embodiment of the present application. Figure 2As shown in the figure, the microstructure presents a typical multiphase mixed morphology. The matrix part is a niobium-hafnium solid solution, in which a large number of impurity phases of uneven sizes are dispersed. These impurity phases are mainly concentrated at the grain boundaries and in the crystals. The impurity phases at the grain boundaries are in the range of 1.2-3.5μm in size, irregular in shape, and partially distributed in clusters; the impurity phase particles in the crystals are relatively small, with a size between 0.3-0.8μm and a spherical shape. Through energy spectrum analysis, these impurity phases are mainly composed of oxides and fluorides, with an average impurity content of 1873±127ppm. In the three-dimensional reconstructed image, the distribution characteristics of the impurity phase in the depth direction can be observed, showing obvious stratification, which is directly related to the unevenness of the melt convection and solidification process in the traditional arc melting process.

[0064] In terms of grain boundary morphology, the grain boundaries of samples prepared by the traditional arc melting method show obvious jagged features, and the width of the grain boundary line is uneven, fluctuating in the range of 0.8-2.2μm. There is an obvious stress concentration area near the grain boundary, which is manifested as a band-shaped area with significant contrast difference, with a bandwidth of about 4.5-6.8μm. The surface roughness of the sample is relatively large, with an Ra value of about 0.42μm, and there are a large number of micropores, with the hole diameter distributed between 0.5-1.8μm. Through surface morphology analysis, it can be seen that the sample has obvious segregation bands, with a width of 15-25μm, extending along the grain boundary direction to form a network distribution. These characteristics indicate that the traditional arc melting process has limited control over impurity elements, and the mass transfer and heat transfer processes inside the melt are not uniform enough.

[0065] Figure 3 A TEM image of a niobium-hafnium alloy provided in an embodiment of the present application. Transmission electron microscopy observations show that the grain boundary structure of the sample exhibits highly regular characteristics, and the grain boundary width is uniform, with an average value of 3.82±0.48nm. The atomic arrangement in the grain boundary region shows obvious periodic changes, and there is no obvious amorphous transition layer. The lattice fringes of the {110} crystal plane can be clearly observed in the high-resolution image, and the fringing spacing is 0.235nm, which is consistent with the theoretical calculation value. The grain orientation relationship on both sides of the grain boundary is clear, and no obvious strain field is observed. Through Fourier transform analysis, the local atomic structure of the grain boundary region shows a regular correspondence, and the atomic displacement at the grain boundary is in the range of 0.12-0.15nm.

[0066] In the area near the grain boundary, a small amount of dispersed nanoscale precipitates were observed. These precipitates were uniform in size with an average diameter of 4.2±0.6nm. The interface between the precipitates and the matrix was clear, showing a specific crystallographic relationship. Through dark field image analysis, the distribution density of these precipitates in the matrix was about 3.8×10 14 pcs / m 3, and most of them are distributed in the intracrystalline position, and the number of precipitated phases at the grain boundaries is significantly reduced. In the high-magnification TEM image, it can be seen that there is a regularly arranged dislocation network at the grain boundary, and the dislocation spacing is about 12.5nm. This dislocation structure is conducive to the stability of the grain boundary. STEM-HAADF imaging of the grain boundary area shows that the atomic number contrast is not obvious, indicating that no obvious element segregation occurs at the grain boundary. Through real-space atomic resolution analysis, the atomic arrangements on both sides of the grain boundary have a good correspondence, and the grain boundary angle is maintained within the ideal value of ±2°.

[0067] Figure 4 An EDS analysis diagram of the distribution of impurity elements provided in an embodiment of the present application. The energy dispersion analysis results show the concentration gradient variation characteristics of the impurity elements within the scanning distance range. The concentration of impurity elements in the traditional method sample drops rapidly within the range of 0-5μm, from the initial 2450ppm to 1650ppm, and then the concentration decrease trend slows down, slowly decreasing to 850ppm within the range of 5-15μm, and stabilizes within the range of 15-25μm, and finally stabilizes at about 820±100ppm. The scanning curve shows obvious exponential decay characteristics, and there is a concentration fluctuation of ±100ppm throughout the scanning range. This concentration distribution pattern shows that there is a significant local enrichment phenomenon of impurity elements in the traditional process, and the enriched area is mainly concentrated within the surface layer of 5μm.

[0068] In the samples prepared by the method of the embodiment of the present application, the concentration of impurity elements is significantly reduced as a whole, and the distribution is more uniform. In the range of 0-5μm, the concentration slowly decreases from the initial 482ppm to 420ppm, and then further decreases to 350ppm in the range of 5-15μm, and finally stabilizes at about 320±50ppm in the range of 15-25μm. The concentration curve shows a relatively gentle trend of change, and the concentration fluctuation is small, maintained within the range of ±50ppm. By quantitatively analyzing the scanning curve, the attenuation coefficient obtained is 0.083μm -1 , much smaller than the 0.312μm of the traditional method -1 , which indicates that the method of the embodiment of the present application significantly improves the distribution uniformity of impurity elements. The fluctuation characteristics of the curve indicate that there is systematic instrument noise in the measurement process, but it does not affect the judgment of the overall trend.

[0069] Figure 5An EBSD analysis diagram of grain boundary orientation distribution provided in an embodiment of the present application. The orientation angle distribution diagram shows the statistical characteristics of grain boundary orientation in the range of 0-60°, which includes the basic Mackenzie distribution and characteristic peaks. In the traditional method sample, characteristic peaks appear at three positions: 38.9° (Σ7), 43.1° (Σ21a) and 50.5° (Σ11), with peak intensities of 0.3, 0.25 and 0.2, respectively, and corresponding half-height widths of 1.2°, 1.0° and 1.1°, respectively. The existence of these characteristic peaks indicates that a certain number of special grain boundaries have been formed in the sample, but the peak shape is wide and the intensity is relatively weak, indicating that the number of special grain boundaries is limited and the orientation relationship is not perfect.

[0070] In the samples prepared by the method of the embodiment of the present application, the characteristic peaks at the same angular position show higher intensity and narrower peak width. The peak intensities corresponding to the Σ7, Σ21a and Σ11 grain boundaries are increased to 0.8, 0.7 and 0.6, respectively, while the half-height width is reduced to 0.8°, 0.7° and 0.8°. The peak shape shows obvious symmetry, the baseline is stable, and the discreteness of the data points is small. By integrating the orientation distribution within the entire angle range, the proportion of special grain boundaries in the total grain boundaries is increased from 23.5% of the traditional method to 42.8%. In the range of 0-15° small-angle grain boundaries, the relative frequency curve is smooth, without obvious abnormal peaks, indicating that no significant subgrain structure is formed in the sample. The number of large-angle grain boundaries near 60° is moderate and the distribution is regular, which has a positive effect on the comprehensive properties of the material.

[0071] Figure 6 An energy spectrum analysis diagram of an impurity phase component provided in an embodiment of the present application. The energy spectrum diagram records the distribution of characteristic peaks in the energy range of 0-20keV. In the traditional method sample, multiple obvious characteristic peaks of impurity elements were observed, mainly including Al at 2.8keV, Fe at 5.2keV, Ni at 7.5keV, Zr at 9.8keV and Hf at 12.4keV. The counting rates of these peaks are relatively high, with the maximum count of the Al peak reaching 1000cps / eV, the Fe peak being 800cps / eV, the Ni peak being 600cps / eV, the Zr peak being 400cps / eV, and the Hf peak being 300cps / eV. Each characteristic peak shows obvious Gaussian distribution characteristics, and the peak shape is complete, but there is a certain degree of overlap, especially in the Fe and Ni peak regions within the range of 5-8keV.

[0072] In the energy spectrum of the sample of the embodiment method of the present application, the intensity of the characteristic peak at the same position is significantly reduced, and the maximum counts of Al, Fe, Ni, Zr and Hf are reduced to about 30% of the original, respectively, and the peak shape is more regular, and the half-height width is generally reduced. The background noise level is low, and the signal-to-noise ratio is significantly improved, which is conducive to the accurate quantification of trace elements. The separation between the peaks is improved, which facilitates accurate peak area integral calculation. Through quantitative analysis of the peaks of the main impurity elements, combined with the corresponding sensitivity factors and matrix corrections, the mass fractions of each element calculated are significantly lower than those of the traditional method samples. The repeatability of the energy spectrum data is good, and the relative standard deviation of multiple measurements is controlled within 3%.

[0073] In summary, in the melt purification treatment of the existing niobium-hafnium alloy smelting process, a medium-frequency electromagnetic field with a constant frequency and a fixed current intensity is usually used for treatment. This simple electromagnetic field control method has the following technical defects: the melt is prone to form a steady-state eddy current zone under the action of the electromagnetic field, resulting in the inability to effectively migrate and separate impurities in the local area. Especially under high temperature conditions where the melt temperature reaches 2480-2510°C, the traditional fixed-parameter electromagnetic field is difficult to adapt to the dynamic changes of physical parameters such as melt viscosity and conductivity. At the same time, due to the use of a three-phase power supply with a symmetrical phase difference arrangement, the electromagnetic force field generated shows strong uniformity in the axial and radial directions. Although the overall stirring of the melt can be achieved, a directional spiral upward flow cannot be formed, resulting in an irregular impurity floating path, and some floating impurities are easily drawn into the deep part of the melt by the eddy current. In addition, if the electromagnetic field is directly turned off after the refining process is completed, the melt will produce violent fluctuations, causing the separated impurities to be re-involved in the melt, reducing the purification effect. In actual production, these technical problems result in uneven distribution of impurities in the melt, low separation efficiency, and poor process stability.

[0074] In response to the above technical problems, the embodiment of the present application adopts a composite control strategy of dynamic frequency modulation and variable current, and adjusts the electromagnetic field parameters in real time through the calculation formula of frequency and temperature coupling to ensure that the intensity of the electromagnetic force always matches the physical properties of the melt. By setting a three-phase power supply with an asymmetric phase difference, a spiral electromagnetic force field with a specific orientation is formed in the melt. This force field distribution can provide a stable motion trajectory for the migration of impurities. At the same time, the axial gradient electromagnetic force field intensity distribution is adopted to avoid the eddy current dead zone under the traditional uniform field strength. In the process, the precise control of the electromagnetic field is achieved through reasonable coil structure design and the arrangement of the flux compensation device. Especially at the end of refining, the exponential law is used to reduce the field strength to avoid violent fluctuations in the melt. This technical solution of multi-parameter coordinated control solves the problem of unsatisfactory electromagnetic field effect in the prior art and significantly improves the impurity separation efficiency.

[0075] Furthermore, an embodiment of the present application also provides a medium frequency electromagnetic field control device, including: a processor, a memory, and a system bus; the processor and the memory are connected via the system bus; the memory is used to store one or more programs, and the one or more programs include instructions, and when the instructions are executed by the processor, the processor executes any of the above methods.

[0076] Furthermore, an embodiment of the present application also provides a computer program product, which, when executed on a terminal device, enables the terminal device to execute any of the above methods.

[0077] It can be known from the description of the above implementation mode that those skilled in the art can clearly understand that all or part of the steps in the above-mentioned embodiment method can be implemented by means of software plus a necessary general hardware platform. Based on such an understanding, the technical solution of the present application can be essentially or partly embodied in the form of a software product that contributes to the prior art. The computer software product can be stored in a storage medium such as ROM / RAM, a disk, an optical disk, etc., including several instructions for enabling a computer device (which can be a personal computer, a server, or a network communication device such as a media gateway, etc.) to execute the methods described in the various embodiments of the present application or certain parts of the embodiments.

[0078] It should be noted that the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments, and the same or similar parts between the various embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part description.

[0079] It should also be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.

[0080] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for controlling impurity elements in the smelting process of niobium and hafnium alloys, characterized in that: include: The niobium and hafnium raw materials are dried in an inert atmosphere, mechanically ground, and melted by vacuum induction heating; Adding refining agents and applying medium frequency electromagnetic fields to purify the melt; After the slagging operation is completed, the target elements are added and the temperature is controlled; It is poured through a preheated draft tube and solidifies quickly.

2. The control method according to claim 1, characterized in that: in, The niobium and hafnium raw materials are dried in an inert atmosphere, mechanically ground, and melted by vacuum induction heating, including: Select high-grade industrial niobium and pure hafnium, and transfer the raw materials into a ball mill for mechanical grinding under argon protection; The smelting is carried out in a medium frequency vacuum induction furnace according to the prescribed melting control procedure, and the inner wall of the smelting crucible is coated with an yttrium oxide protective layer.

3. The control method according to claim 1, characterized in that: in, Adding refining agents and applying medium frequency electromagnetic fields for melt purification, including: Adding a refining agent consisting of calcium fluoride, yttrium oxide and magnesium fluoride to a molten niobium-hafnium alloy; Refining is carried out under the condition of applying a medium-frequency electromagnetic field, so as to utilize electromagnetic force to generate directional flow to promote the aggregation and floating of inclusions; The slagging operation is completed under the protection of argon.

4. The control method according to claim 3, characterized in that: in, Refining is carried out under the condition of applying medium frequency electromagnetic field, including: The induction coil is made of a water-cooled copper tube, and the induction coil is evenly wound along the axial direction of the crucible; A high-purity quartz glass insulating sleeve is arranged between the coil and the crucible, and the electromagnetic field is controlled by adjusting the frequency and current intensity.

5. The control method according to claim 4, characterized in that: in, Refining under the condition of applying a medium frequency electromagnetic field also includes: The electromagnetic force distribution is controlled by adjusting the phase difference of the three-phase power supply, and the phase difference of the three-phase power supply is set to a reference phase, an advanced reference phase and a lagging reference phase respectively to form a spirally rising electromagnetic force field.

6. The control method according to claim 4, characterized in that: in, Refining under the condition of applying a medium frequency electromagnetic field also includes: In the early stage of the refining process, a high electromagnetic field intensity is maintained for strong stirring, and then the electromagnetic field intensity is gradually reduced. At the end of refining, the electromagnetic field intensity is stabilized within a specific range and the melt flow rate is controlled.

7. The control method according to claim 1, characterized in that: in, After the slagging operation is completed, the target elements are added and the temperature is controlled, including: adding alloy elements including tantalum and tungsten at target purity to the melt, and controlling the feeding rate by a feeding device; The alloy elements are evenly distributed by stirring through a medium-frequency electromagnetic field, and the temperature is raised, kept and lowered in sequence.

8. The control method according to claim 1, characterized in that: in, Casting through preheated draft tubes and rapid solidification, including: The guide tubes of different lengths and preheating temperatures are selected according to the hafnium content. The guide tubes are made of high-purity zirconium oxide material and are preheated by electromagnetic induction heating. The outside is covered with a heat-insulating protective layer and is cast under argon protection using a bottom pouring system.

9. The control method according to claim 8, characterized in that: in, Choose the draft tubes of different lengths and preheating temperatures according to the hafnium content, including: The preheating temperature of the guide tube is determined according to the hafnium content. When the hafnium content is lower than a preset value, a low preheating temperature is configured, and when the hafnium content is higher than a preset value, a high preheating temperature is configured. Preheating adopts medium-frequency induction heating, and the outside of the guide tube is coated with a protective layer made of a composite material of zirconium oxide and yttrium oxide.

10. The control method according to claim 8, characterized in that: in, The bottom pouring system is used for pouring under argon protection, including: The bottom pouring system uses a water-cooled copper mold to rapidly solidify during the pouring process, and the pouring chamber is filled with high-purity argon gas and maintained at a constant pressure. The pouring process is completed by controlling the pouring rate and the temperature and flow rate of cooling water.